EFFECTIVE LEADERSHIP QUALITIES IN PHYSICAL EDUCATION AND SPORTS - Sharma, Anu; Bala, Jyoti; Singh, Davinder (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Through the practice of leadership, a person can persuade others to work towards a common goal and guide the organization towards greater coherence and coherence. Excellent leaders may be developed, not born. You can become a successful leader if you have the motivation and willpower. A never-ending process of self-study, education, training, and experience is how good leaders are created. (Jago, 1982). We are aware of the characteristics that can affect our behaviour, though. Trait Leadership is what we call this (Jago, 1982). In that it used to be commonplace to think that leaders were more likely to be born than created. In particular, physical education is examining closely how its professional preparation programmes are run. New curricula are being prepared, new courses are being developed, new teaching techniques are being tried out and assessed, and understanding of physical education is expanding thanks to research. The liberal arts and well-grounded studies are becoming more and more important to students in professional preparation programme nowadays. They can significantly benefit the entire educational community thanks to their training. Many books and articles have been written detailing what it takes to run a company effectively. Some academics and authors contend that outstanding leaders have particular skills or abilities, while others assert that it all comes down to personality. Others claim that behaviors, rather than intentions or thoughts, are what matter. Leaders are people with extraordinary character who can help others get through a difficult situation.